Quality-of-Life Outcomes following Surgical Treatment of Ménière's Disease: A Systematic Review and Meta-analysis. (February 2019) - Ballard, Daniel P.; Sukato, Daniel C.; Timashpolsky, Alisa; Babu, Seilesh C.; Rosenfeld, Richard M.; Hanson, Matthew
Objective: Several surgical interventions are offered to patients with Ménière's disease (MD) who fail medical management. Although outcomes have historically been reported according to American Academy of Otolaryngology—Head and Neck Surgery guidelines, patient-reported outcome measures (PROMs) are increasingly used to evaluate treatments. This study reviews PROMs used to assess surgical treatments for MD and compares the effect of each intervention based on PROM scores. Data Sources: PubMed, EMBASE, CINAHL, and Web of Science. Review Methods: This is a systematic review and meta-analysis of English-language studies that reported PROMs for surgical treatments of MD. Two independent investigators assessed study eligibility, rated the quality using Methodological Index for Non-Randomized Studies (MINORS), and abstracted data for comparative analysis. A random-effects model was used for meta-analysis of pooled data. Results: Of 148 unique studies identified, 11 satisfied inclusion criteria. The Ménière's Disease Outcome Questionnaire (MDOQ) was the most commonly used survey. Interventions included intratympanic gentamicin, vestibular nerve section, endolymphatic sac surgery, and labyrinthectomy. Pooled analysis of 8 studies that used the MDOQ instrument demonstrated statistically significant improvements in quality of life but did not identify a difference between destructive and nondestructive procedures. Conclusion: Although our review shows significant improvements in PROM scores for both destructive and nondestructive interventions, there was no significant difference noted between treatment types. We cannot draw conclusions regarding the comparative effectiveness of specific interventions, and the results do not account for placebo effects or the natural history of the disease. Further investigation with randomized controlled trials should be considered in future studies.